DUKUNGAN ORANGTUA, EFIKASI DIRI PENGAMBILAN KEPUTUSAN KARIER, DAN PLANNED HAPPENSTANCE PADA SISWA SEKOLAH MENENGAH PERTAMA - Amini, Dara Suci; Salim, Rose Mini Agoes (Konsorsium Psikologi Ilmiah Nusantara (KPIN), 2020)
Abstract ?Adolescence is an important period for career development. Parent support and adolescent?s skills in seeking career opportunities from unexpected encounters contribute to adolescent?s self-efficacy in career decision making. The present study examined the mediating role of planned happenstance in the relationship between career-related parent support and self-efficacy in career decision making among junior high school students. Participants comprised of 136 junior high school students. The instrument used in this study were the Indonesian translations of Career-Related Parent Support Scale, Career Decision Self-Efficacy-Short Form, and Planned Happenstance Career Inventory. Results suggested that career-related parent support affects career decision-making self-efficacy directly or through the mediation of planned happenstance. The study concludes by outlining the importance of future studies to analyze the relationship between career-related parent support and planned happenstance. Abstrak ? Masa remaja merupakan masa yang sangat penting dalam pengembangan karier. Dukungan orang tua dan juga keterampilan remaja dalam memanfaatkan peristiwa tak terduga sebagai peluang karier memengaruhi efikasi diri dalam membuat keputusan karier. Penelitian ini bertujuan untuk mengetahui peran planned happenstance dalam memediasi hubungan career-related parent support dan efikasi diri pengambilan keputusan karier pada siswa SMP. Subjek penelitian ini terdiri dari 136 siswa SMP. Alat ukur yang digunakan adalah Career-Related Parent Support Scale, Career Decision Self-Efficacy-Short Form, dan Planned Happenstance Career Inventory yang diadaptasi ke dalam Bahasa Indonesia. Hasil menunjukkan bahwa career-related parent support memengaruhi efikasi diri pengambilan keputusan karier secara langsung maupun melalui mediasi planned happenstance. Penelitian selanjutnya dapat menganalisis hubungan career-related parent support dan planned happenstance.